Undesirable but Unreturnable Migrants: the Challenges of Dealing with Criminal Migrants in Need of Protection : A Comparative Analysis of Australia, Belgium and Canada - Barboza, Júlia Zomignani (Human Rights and Humanitarian Law E-Books Online, Collection 2026., 2025)
This book studies how States regulate the situation of migrants in need of international protection who have a criminal background or pose a threat to public order. Regulating the situation of these migrants is a challenge to States, which may sometimes resort to measures that violate human rights. The book thus evaluates the solutions applied, identifying best practices and suggesting a possible human rights compliant solution for this situation.